2020
DOI: 10.1108/ijchm-02-2020-0134
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationships between distances and herd behavior in online reviews: the moderating effects of hospitality experience

Abstract: Purpose This study aims to investigate the determinants of herd behavior in online hotel service evaluations, focusing on the cultural and geographic distance characteristics of customers. Design/methodology/approach On the basis of 381,462 TripAdvisor reviews of hotels in the USA written by more than 100,000 customers from 92 countries, this study uses the empirical analysis to explore the collective roles of cultural distance, geographic distance and hospitality experience on herd behavior in online hotel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…For instance, during the early COVID-19 outbreak, many people were uncertain about whether to stock up; nevertheless, when they noticed that a majority of others were engaging in panic buying, they followed such a behavior (Loxton et al, 2020). Likewise, when individual users are uncertain about whether to share a social media post or endorse an online review, they tend to imitate others; if they observe many "likes" of the post and many favorable online reviews, they will follow the crowd and perform the same behavior (Mattke et al, 2020;Xue et al, 2020). These studies demonstrate that perceived herd may largely increase an individual's likelihood of performing a behavior about which he or she is previously uncertain.…”
Section: The Moderating Role Of Perceived Herdmentioning
confidence: 99%
“…For instance, during the early COVID-19 outbreak, many people were uncertain about whether to stock up; nevertheless, when they noticed that a majority of others were engaging in panic buying, they followed such a behavior (Loxton et al, 2020). Likewise, when individual users are uncertain about whether to share a social media post or endorse an online review, they tend to imitate others; if they observe many "likes" of the post and many favorable online reviews, they will follow the crowd and perform the same behavior (Mattke et al, 2020;Xue et al, 2020). These studies demonstrate that perceived herd may largely increase an individual's likelihood of performing a behavior about which he or she is previously uncertain.…”
Section: The Moderating Role Of Perceived Herdmentioning
confidence: 99%
“…On the other hand, online reviews contain a large number of aspects in a short time interval. Second, we find that even the same aspect has significant differences in user attention in different brands, indicating a preference for consumer behavior (Xue et al, 2020;Kim et al, 2010). We also found that users' reviews posted after a short interval experience have a significant sentiment tendency.…”
Section: Exploring the Distribution Regularitiesmentioning
confidence: 52%
“…Crowding in a marketing campaign means that there are a large number of potential purchasers focused on the target product (Noone and Mattila, 2009a). Following the attention of the group and imitating its behavior helps reduce perceived uncertainty in purchase decisions (Xue et al, 2020). Studies on bidding behaviors have also proposed that potential product competitors can reduce consumers' perceptions of decision uncertainty because of the fact that product competitors increase consumers' confidence in the product (Heyman et al, 2004).…”
Section: Online Crowding Perceived Price Attractiveness and Perceived...mentioning
confidence: 99%